Hubungan Antara Stress Kerja Dan Beban Kerja Dengan Kepuasan Kerja Karyawan PT X Divisi Produksi - Najmah Faiha Nurul Syahidah; Risa Ayu Maulina; Tanti Nurfadilah; Lucky Purwantini (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
Problems commonly faced in the world of work, where high levels of stress and workload can have a negative impact on employee mental well-being and productivity. Employees who are dissatisfied with their jobs tend to show negative attitudes towards their tasks and may experience higher levels of stress while carrying out their jobs. The aim of the research is to analyze the relationship between work stress and workload on job satisfaction of production operator division employees at PT. Epson Indonesia. This research uses a quantitative approach, a population of 134 employees using Purposive Sampling Technique. The data collection method in this research uses a data collection instrument in the form of a psychological scale. Data analysis techniques use normality tests, linearity tests, correlation tests, with the help of SPSS version 21 for Windows. The results of hypothesis testing using the Pearson product moment correlation test obtained a sig = 0.064 for work stress and a sig = 0.005. While work stress has a significant positive effect on job satisfaction, at the same time workload has a clear negative effect on job satisfaction.